The Crime of homosexual carnal access in Colombia Between homophobia and psychiatric medicine and the legal patriarchal order (2008)
In the nineteenth century, psychiatric medicine determined the homoeroticism, invented the homosexual and proposed cures for him. In 1936 the Colombian Penal Right criminalized those subjects. Beginning from the contradictions between those institutions,